Time and Space in Tzeltal: Is the Future Uphill? - Brown, Penelope (Frontiers in Psychology, 2012)
Linguistic expressions of time very often draw on spatial language, prompting one to wonder whether cultural specificity in spatial language and cognition is reflected in thinking about time. In the Mayan language Tzeltal, spatial language relies heavily on an absolute frame of reference utilizing the overall slope of the land, distinguishing an uphill/downhill axis and an orthogonal ‘crossways’ axis on the basis of which objects at all scales are located. Does this absolute system for calculating spatial relations carry over into construals of temporal relations? This question was explored in a study where Tzeltal consultants produced temporal expressions and performed two different nonlinguistic temporal ordering tasks. The results show that at least five distinct schemata for conceptualizing time underlie Tzeltal linguistic expressions: (i) deictic ego-centered time (ii) time as an ordered sequence (e.g. ‘first’/‘later’), (iii) cyclic time (times of the day, seasons), (iv) time as spatial extension or location (e.g., ‘entering/exiting July’), and (v) a time vector extending uphillwards into the future. This paper examines the conditions promoting one or another of these schemata, and argues that systematic and consistent use of spatial language in an absolute frame of reference does not necessarily transfer to consistent absolute time conceptualization in the nonlinguistic tasks; time appears to be more open to alternative construals.